Conflicts over Customary Rights of Indigenous Communities in The National Capital City Development Project - Nina Sri Mulyani; Rita Alfiana (International Journal of Science and Environment (IJSE), 2026)
This study examines agrarian conflicts in the development of the Indonesian National Capital (IKN) in East Kalimantan, with a focus on the customary rights of indigenous peoples. Normatively, Article 18B paragraph (2) of the 1945 Constitution and Article 3 of the UUPA have provided recognition to indigenous peoples and their customary rights. However, the implementation of this recognition has not been effective. Dependence on administrative recognition through Regional Regulations (Perda), lengthy mechanisms for proving customary rights, and the paradigm of accelerated development have led to marginalization, loss of living space, and legal uncertainty. This study uses normative legal methods with a statutory, conceptual, and case approach and is analyzed through the Theory of Recognition and the Theory of Development Law. The results indicate that although the national legal framework has regulated customary rights, the practice of IKN development still places these rights as administratively conditional rights. The absence of a Perda recognizing customary communities means that customary land that has not been formally designated is treated as state land. AMAN data from 2025 recorded 110 agrarian conflicts, including the Balik Sepaku, Balik Pemaluan, and Paser Maridan cases, demonstrating the disharmony between legal norms and their implementation. Therefore, a structural and paradigmatic transformation of agrarian law is needed through the ratification of the Customary Law Communities Law, accelerated regional regulation formation, and participatory mapping of customary territories.